Estado nutricional e produção de massa seca da alfafa em função de doses de Potássio em dois solos - Orioli Júnior, Valdeci; Coutinho, Edson Luiz Mendes [UNESP]; Coutinho Neto, André Mendes [UNESP]; Cardoso, Saulo Strazeio [UNESP] (My University, 2014)
Potassium fertilization is very important to alfalfa crop in terms of yield, quality and persistence of forage, especially on soils naturally poor K. Thus, to assess the effects of K fertilization in alfalfa production and nutritional status, was carried out an experiment in a greenhouse using samples of a Dystrophic Oxisol medium texture (LV) (0.6 mmolcdm-3K) and a Dystrophic Ultisol sandy/medium texture (PVA) (2.2 mmolcdm-3K). A completely randomized design in a factorial arrangement 6 × 2 (six K rates and two soils) was used, with four replications. The K rates used were: 0, 25, 50, 100, 150 and 200 mg kg-1K. Potassium fertilization increased K content in soil and shoots. Dry matter production was increased with the K addition. However, in the PVA, this occurred only in the second cut. In LV, potassium fertilization increased N concentration in alfalfa shoots in both cuts. Plants with K concentration around 10 g kg-1had typical symptoms of this nutrient deficiency. The K critical levels of K in soil and shoots were 1.8 mmolcdm-3and 16.7 g kg-1, respectively.
Nutritional status and dry mass production of alfalfa in function of Potassium rates in two soils
Keywords: Critical level; Medicago sativa; Plant nutrition; Potassium fertilization